Does Nurturing "Zest for Life" Also Lead to Nurturing "Resilience"? (Sains Humanika, 2025)
It has been revealed that "resilience" is involved in the ability to overcome adverse experiences in childhood. However, the school education curriculum does not clearly state how to foster resilience, and it cannot be said that there has been sufficient discussion about how to foster the resilience necessary for recovering after a disaster or adversity. The Ministry of Education, Culture, Sports, Science and Technology, which oversees school education in Japan, has set the educational philosophy as acquiring "the ability to live." The educational philosophy of each school is left to the principal, and the policy of educational activities is set by each school principal, which is shared and known to teachers and staff, and then put into practice. This study posed the research question of whether "resilience" can also be fostered by cultivating "the ability to live," and aimed to explore the daily educational activities of schools that correspond to cultivating "resilience." We interviewed eight principals. The elementary and junior high school principals with the aim of exploring the daily educational activities of schools that correspond to cultivating "resilience." The principals are working to cultivate "the ability to live" from both the perspectives of subject instruction and student guidance so that children can withstand the stress of adversity, and at the same time, they aim for the school to function as a safe and secure place that protects children, like a shield. It was shown that school practices are not only aimed at disaster prevention education, but also at improving everyday problem-solving skills and enriching humanity.
Keywords: school education, zest for life, resilience, prevention